Financial constraints and productivity: Evidence from euro area companies*. (27th February 2018) - Ferrando, Annalisa; Ruggieri, Alessandro
Abstract: Using firm‐level data from the Bureau van Dijk‐ Amadeus database, we study the relation between firms' financial structure, access to external finance, and total factor productivity in several euro area countries along the period 1995–2011. To do so, we build a synthetic indicator of financial constraints using an a priori classification based on specific firm characteristics and measures of financial pressure, and we embed it into a production equation, which controls for the endogenous relation between labour decisions and productivity innovations. We find a negative and significant estimate for the elasticity of total factor productivity with financial constraints of −18%. This effect significantly amplifies in small, young, and private companies, it is likely to persist over time, and it increased during the recent financial crisis. A counterfactual exercise shows that peripheral countries are likely to gain between 19% and 22% of their average total factor productivity from free access to finance. Results are robust to several robustness checks.